CLINICAL STAGE STUDENTS’ READINESS AND PERCEPTION TOWARDS SELF-DIRECTED LEARNING - Syska Widyawati; Setyawati Budiningsih; Anwar Jusuf (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Self-directed learning (SDL) as part of student-centered learning, has been applied in medical education curriculum in Indonesia since the Competency-Based Curriculum was introduced. Students’ perception towards SDL concept in relation to clinical stage and how it is applied are important to identify problems from students’ point of view. This study aimed to see SDL readiness and its correlation to academic achievement; and to obtain student perceptions towards SDL.Methods: A cross-sectional quantitative study was conducted in the Faculty of Medicine Universitas Indonesia (FMUI) from April to June 2013, involving 209 of year 4 students to see SDL readiness and its correlation to academic achievement. Qualitative methods with phenomenological approaches were used to obtain student perceptions of SDL.Results: 71.3% of students were in the category of ready for SDL with a mean score of 57.03 (SD 7.416). Among students’ characteristics, significant mean difference was found in type of education program. The international class group had a higher mean score than the regular group (p 0.014). SDLRS scores did not correlate with student academic grades. Students’ perceptions towards SDL were in accordance with known concepts, and students preferred SDL rather than teacher-centered learning in the clinical stage with suggestions of improvement in some areas.Conclusion: Clinical stage students were ready to conduct SDL. International class students seemed more ready for SDL. Students at year 4 clinical stage had good perception of SDL. This positive perception would provide sufficient readiness for the implementation of SDL in medical education.